Beyond Training: Worker Agency, Informal Learning, and Competition - Mikko Silliman; Alexander Willén (Institute of Labor Economics (IZA), 2025)
This paper reconsiders how labor market competition shapes skill development — integrating the perspectives of both firms and workers. We show that competition serves as a catalyst for learning. It creates outside opportunities which incentivize workers to invest in their own skills, and it imposes innovation pressure that raises the value of training for firms. Using linked Norwegian survey and administrative data together with vignette experiments, we find that workers in more competitive markets accumulate skills faster than workers in concentrated markets—primarily through informal learning—and that these gains are concentrated in higher-order, transferable skills. Firms in competitive environments also invest more in formal training, treating it as a strategic necessity rather than a dispensable cost. Experimental evidence complements these findings by showing that both workers and managers expect greater returns to learning and human capital investments in competitive markets. Together, these results challenge the canonical view of competition as a source of market failure in training and instead highlight its role in facilitating both worker-led and firm-led investments in human capital.
Keywords: J24; J31; J42; 330; competition; human capital; skills